2019
DOI: 10.1128/aem.03029-18
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Function of the N -Acetyltransferase SatA That Detoxifies Streptothricin in Bacillus subtilis and Bacillus anthracis

Abstract: Acylation of epsilon amino groups of lysyl side chains is a widespread modification of proteins and small molecules in cells of all three domains of life. Recently, we showed that Bacillus subtilis and Bacillus anthracis encode the GCN5-related N-acetyltransferase (GNAT) SatA that can acetylate and inactivate streptothricin, which is a broad-spectrum antibiotic produced by actinomycetes in the soil. To determine functionally relevant residues of B. subtilis SatA (BsSatA), a mutational screen was performed, hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Aminoglycoside (ant(6)-Ib (867 bp)) and streptothricin resistance (satA) genes were also located within the multidrug resistance island (Figure 1A). Streptothricin acetyltransferase A (satA) is frequently reported in Gram positive bacilli [112] and shares less than 40% identity with the streptothricin acetyltransferase A (sat4) reported in Campylobacter [52,111,113]. Plasmid replication proteins within the MDRGI suggest a plasmid as the insertion vehicle of the resistance genes.…”
Section: Discussionmentioning
confidence: 99%
“…Aminoglycoside (ant(6)-Ib (867 bp)) and streptothricin resistance (satA) genes were also located within the multidrug resistance island (Figure 1A). Streptothricin acetyltransferase A (satA) is frequently reported in Gram positive bacilli [112] and shares less than 40% identity with the streptothricin acetyltransferase A (sat4) reported in Campylobacter [52,111,113]. Plasmid replication proteins within the MDRGI suggest a plasmid as the insertion vehicle of the resistance genes.…”
Section: Discussionmentioning
confidence: 99%
“…Genes fosB that encoding fosfomycin resistance protein [70], tetracycline resistance genes tet(M) and tet(O) encoding paralogs of the translational GTPase, the elongation factor EF-G were present in all of the tested genomes, through which tetracycline was actively removed from the ribosome of bacteria [71,72], and phylogenetic analyses suggested that fosB genes of Lysinibacillus were likely acquired via cross-family gene exchange or HGT events (Figure S14). Genes encoding aminoglycoside adenylyltransferases that adenylated streptomycin and spectinomycin [73] were present in all of the tested genomes, except for L. contaminans DSM 25,560 and L. sphaericus OT4b.31, whereas genes satA encoding N-acetyltransferases that inactivated streptothricin via acetyl-CoA-dependent lysine acetylation [74,75] were only found in strains of L. pakistanensis and strain L. xylanilyticus t26, likely acquired via cross-order HGT (Figure S15). Genes encoding beta-lactamases involved in resistance to beta-lactam antibiotics were present in all tested genomes, except for L. contaminans DSM 25560, acquired probably via cross-class HGT from members of Clostridiales or Tissierellales (Figure S16).…”
Section: Resistance To Antibiotics and Toxic Metalsmentioning
confidence: 99%
“…5B). In addition, a conserved aspartate (D160) was found to be necessary for dimerization (98). Together, these data help shape our understanding of how, in general, GNATs recognize and bind their ligand.…”
Section: Streptothricin-modifying Gnatsmentioning
confidence: 78%
“…To gain insights into streptothricin binding to SatA, a detailed study of the B. anthracis SatA (BaSatA) enzyme was performed (98). The crystal structure of BaSatA displays a typical GNAT architecture with AcCoA situated in a V-shaped cleft.…”
Section: Streptothricin-modifying Gnatsmentioning
confidence: 99%